Targeting Calcium Homeostasis in Myocardial Ischemia/Reperfusion Injury: An Overview of Regulatory Mechanisms and Therapeutic Reagents - Wang, Ruiying; Wang, Min; He, Shuaibing; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2020)
Calcium homeostasis plays an essential role in maintaining excitation-contraction coupling (ECC) of cardiomyocytes, including calcium release, recapture and storage. The disorder in any process of the calcium homeostasis may affect heart function and then develop into a variety of heart diseases. Myocardial ischemia/reperfusion (MI/R) injury may occur after revascularization that treats coronary heart disease and is a complex pathological process, which is the main cause of increased mortality and disability after coronary heart disease treatment. However, the current treatment methods and drugs for MI/R injury are very scarce, and the treatment effect is not ideal and has limitations. Studies have shown that MI/R injury can cause calcium overload, and calcium overload can further aggravate MI/R injury. Therefore, we review the critical regulators of calcium pathways and their regulation on MI/R injury and draw an intuitive and understandable diagram of the calcium homeostasis pathway. And we also summarize and analyze the calcium pathway-related or MI/R drugs under research or marketing by searching Therapeutic Target Database and PubMed Database. The data showed that about two fifth of the drugs used to treat MI/R injury involve in calcium signaling pathways, and nearly one sixth of the calcium-related drugs are used to treat MI/R injury. We emphasize the relevance of further detailed investigation of MI/R injury and calcium homeostasis and the therapeutic role of calcium homeostasis on MI/R injury, which builds a bridge between MI/R injury's basic research and clinical applications.